Reforma agrária: desafios enfrentados pelos assentamentos rurais alagoanos na aplicação das políticas públicas. - Silva, Roossélia Pontes (2009)
The present study had as objective she analyzes on the challenges faced for the application of the public politics in the from Alagoas rural establishments the results appear for a improvement in the life conditions and of income of the seated families, however not in your totality, many establishments that face problems that were perpetuated exist and that they started to do part of the daily of the man of the field, different dimensions could be observed, among them the initiative as the fight for public politics as construction of schools, health centers and etc. It could be noticed the appearance of innovative initiatives on the part of seated them and your associations in the sense of having larger participation, seeking to intervene more intensively in search of the development of the family agriculture arriving in some cases, to face local the constituted power under an oligarchy politic traditionally that if of the costumed and of the coercion to assure the control of the local politics and of the residents of the municipal districts where they are located the establishments, but in those cases they were singular initiatives that didn't contemplate every universe of the seated areas. On the other hand it was evident the poverty, and previsible situation, but a lot of times forgotten, and little it is counted as a quality education, built highways, health centers and etc. everything that contributes to the development of the areas of rural establishments. We consisted that there is a diversity of problems that you/they appeared before the creation and they continued later, mainly for not getting immediate solutions and therefore the problems became larger as for instance the access to the economical market, the drainage of the production, the technicians' lack to lead the technique improvement to be used in the agricultural cultivation and the projects very distant of the lived reality.